Increased sensorimotor network connectivity associated with clozapine eligibility in people with schizophrenia. (30th May 2018) - McNabb, Carolyn Beth; Sundram, Frederick; Soosay, Ian; Kydd, Robert R.; Russell, Bruce Roy
Abstract: Schizophrenia is a heterogeneous disorder that exhibits variable responsiveness to treatment between individuals. Here we conducted a resting-state functional magnetic resonance imaging (rs-fMRI) study to determine whether resistance to first-line antipsychotics is reflected in resting-state connectivity. rs-fMRI data were collected from 15 people who had failed to respond to first-line antipsychotics (clozapine-eligible) and 10 first-line treatment responders (FLR). Image pre-processing and analysis were performed using FMRIB's software library (FSL). Data was decomposed into spatial and temporal components using independent components analysis. Connectivity within each independent component was compared between groups using t -tests and the Bonferroni correction for multiple comparisons. Gender was added as a covariate. Clozapine-eligible individuals exhibited enhanced functional connectivity within the sensorimotor network compared with FLR. Those eligible for clozapine showed additional connectivity with the precuneus compared with FLR. No other comparisons reached statistical significance and no effect of gender was observed. These data reveal differences in functional connectivity between FLR and those eligible for clozapine and suggest that greater connectivity between the SMN and precuneus may be indicative of treatment resistance in people with schizophrenia. Highlights: Sensorimotor connectivity is increased in non-responders to antipsychotics. Dysconnectivity was seen in the precuneus when compared with first-line responders. Dysconnectivity could be a marker of treatment resistance in schizophrenia.